World Wide Web and history. Risks, challenges and opportunities - Dvořák, Tomáš (Dějiny – teorie – kritika, 2014)
The aim of Tomáš Dvořák's study is to summarize the basic parameters of the debate on the relationship between history and the Internet, which has been taking place over the last few years mainly in the German-speaking environment. The author draws attention to the fact that the entry of history into the world of hypertext is associated with a number of doubts and concerns about the future of the discipline itself. He acknowledges that the inclusion of hypertext online history among the standard outputs of historians' work will entail new demands on the training of authors and the expansion of their competences. However, according to Dvořák, historical research has already found itself on the Internet, and it is therefore necessary not to merely passively follow this trend, but to actively influence it. For this reason, for example, the author recommends incorporating Wikipedia's creation of fact into the teaching of history, while encouraging historians and historians to participate in the cultivation of this online encyclopedia.